Bilateral Ureteroarterial Fistula: A Case Report and Review of Literature. Issue 3 (July 2016) - Melegari, Sara; Paparella, Stefano; Follini, Matteo L.; Cappellano, Francesco; Ciotti, Mariano G.; Giollo, Alessandro; Marzorati, Giuliano; Airoldi, Flavio; Losa, Sergio; Verweij, Fabrizio
Ureteral arterial fistula (UAF) is an uncommon condition characterized by a direct fistulous communication between a ureter and an iliac artery resulting in bleeding into the ureter, which can be massive and life-threatening because of hemodynamic instability, as confirmed by the high mortality rate (7-23% overall). This condition is actually increasing in frequency because of its relation to predisposing factors such as vascular pathology, previous radiation therapy, previous surgery, and necessity of ureteral stenting. Diagnosis is often challenging, as in most patients, the only symptom is hematuria and the treatment may require a multidisciplinary approach, including the expertise of the urologist, vascular surgeon, and interventional radiologist. Endovascular approach offers advantages over open surgery decreasing morbidity (reduced risk of injury to adjacent structure) and shortening hospital staying. There is no consensus regarding the safety of intentional occlusion of the hypogastric artery: proximal occlusion of a hypogastric artery typically produces little or no clinical symptoms due to well-collateralized pelvic arterial networks. On the contrary, significant complications, such as colonic ischemia, spinal cord paralysis, buttock claudication, or erectile dysfunction, are well-recognized adverse events after hypogastric artery embolization, especially in bilateral cases. We describe our experience of a bilateral UAF treated with bilateral endvascular approach.